Hydrothermal Synthesis and Photocatalytic Properties of Graphene@Ag/AgSb2O5.8 Composites: Reaction Laws of the Composites in Sintering Process - Haomei Liu; Xihai Hao; Yuejun Liu; Aiguo Yan (Advances in Materials Science and Engineering)
Single-phase silver antimonite have quite low oxidation and reduction potential because of the easy recombination of photogenerated electrons and holes. In the study, a novel ternary graphene@Ag/AgSb2O5.8 (G @Ag/ASO) visible-light-driven photocatalyst was successfully synthesized by a simple hydrothermal method. The morphology, structure, and chemical composition of G @Ag/ASO and its sinters at different temperatures in the air atmosphere were systematically characterized by a range of techniques. Reaction laws of the composites in the sintering process have been revealed based on the Ellingham diagram. The photocatalytic degradation of rhodamine B (RhB) dye and tetracycline hydrochloride (OTC-HCl) by the as-synthesized photocatalyst was investigated under visible light irradiation. The G@Ag/ASO-500 (the sinter at 500°C) exhibits degradation efficiency of 80% for RhB and 85% for OTC-HCl in 120 min, higher than those for AgSb2O5.8 (20% and 24%, respectively). The graphene-enhanced Ag-loaded AgSb2O5.8 model is proposed and reasonably accounts for the high-efficiency electron-hole transfer mechanism through four contact potentials and the crucial role of graphene sheets on the surface of the composites. The present study provides a new perspective for enhancing photocatalytic performance.